On Type I Singularities of the Local Axi-Symmetric Solutions of the Navier-Stokes Equations - Seregin, G; Sverak, V (2009)
Local regularity of axially symmetric solutions to the Navier-Stokes equations is studied. It is shown that under certain natural assumptions there are no singularities of Type I. © Taylor and Francis Group, LLC.